Apuleius on the Heaven: A Question of Authority - Bowen, Alan C. (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2022)
Apuleius’ De mundo pr. 1–3.4 is a loose paraphrase in Latin of the Περὶ κόσμου 391a1–392b14, a treatise once thought to be by Aristotle. By focusing on differences between these two works, I aim to develop some working hypotheses that situate the De mundo in relation to critical disagreements in the second century AD about the heaven, what constitutes knowledge of it, and how this knowledge is to be gained.